2012
DOI: 10.1186/2191-0855-2-41
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of the ability of Burkholderia sp. USM (JCM 15050) PHA synthase to polymerize 4-hydroxybutyrate monomer

Abstract: The nutrition-versatility of Burkholderia sp. strain USM (JCM 15050) has initiated the studies on the use of this bacterium for polyhydroxyalkanoate (PHA) production. To date, the Burkholderia sp. has been reported to synthesize 3-hydroxybutyrate, 3-hydroxyvalerate and 3-hydroxy-4-methylvalerate monomers. In this study, the PHA biosynthetic genes of this strain were successfully cloned and characterized. The PHA biosynthetic cluster of this strain consisted of a PHA synthase (phaC), β-ketothiolase (phaA), acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…, ). According to Lau and Sudesh (), Burkholderia sp. USM () was unable to produce PHA containing 4HB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ). According to Lau and Sudesh (), Burkholderia sp. USM () was unable to produce PHA containing 4HB.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of 4HB into PHA was initially detected in R. eutropha (Kunioka et al , 1989. According to Lau and Sudesh (2012), Burkholderia sp. USM (JCM15050) was unable to produce PHA containing 4HB.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cultivation of the recombinant strain Ralstonia eutropha PHB ‐4 on fructose and 4MV resulted in cell concentration of 1.5 g L −1 and PHA content of 46% of CDM . In a study of the recombinant strain C. necator PHB ‐4 , the mass fraction of P(3HB‐ co ‐3H4MV) in CDM and cell biomass yield were about 40% and 1.6 g L −1 , respectively . Selection of leucine resistant mutants did not result in high yields: cell concentration and polymer content were 1.5–1.7 g L −1 and 51–55% of CDM, respectively, and 3 HV and 3H4MV molar fractions were low (about 0.4–1.7 and 0.5–0.9 mol%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…They found that fatal deterioration was not observed for copolymer containing 3H4MV molar fraction higher than 14 mol%. These copolymers were mainly produced by genetically modified strains, [12][13][14][15] wild-type microorganisms being used in fewer studies. [16][17][18][19] A review of the literature showed the scantiness of the data and the difficulty of achieving both high cell concentrations and large yields of the copolymer, on the one hand, and high molar fractions of 3H4MV, on the other (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Сравнительно недавно в литературе появились данные по синтезу сополимерных ПГА, содержащих в своем составе мономеры 3-гидрокси-4-метилвалерата (3Г4МВ) (Dai et al, 2007;Tanadchangsaeng et al, 2009;Saika et al, 2011). К настоящему времени в качестве продуцентов этих сополимеров в основном описаны генетически модифицированные штаммы (Chia et al, 2010;Tanadchangsaeng et al, 2009;Saika et al, 2011;Lau et al, 2011) и в меньшей степени природные микроор-ганизмы (Tanadchangsaeng et al, 2009;Lau et al, 2010Lau et al, , 2011Lau, Sudesh, 2012), обладающие такой способностью. В серии работ описаны условия синтеза сополимеров, содержащих мономеры 3Г4МВ, на различных субстра-тах: глюкозе (Tanadchangsaeng et al, 2009;Saika et al, 2011;Lau et al, 2011;Lau, Sudesh, 2012), валерате, пропионате (Lau et al, 2010), Примечание: Мч -среднечисловая молекулярная масса, Мв -средневесовая молекулярная масса, ПД -полидисперсность, Сх -степень кристалличности, Тстекл -температура стеклования, Ткрист -температура кристаллизации, Тпл -температура плавления, Тдегр -температура термической деградации, «-» -не обнаружено.…”
unclassified